PENGEMBANGAN MEDIA FLIPBOOK DIGITAL BERBASIS KEARIFAN LOKAL SATUA BALI I CUPAK GERANTANG UNTUK SISWA SEKOLAH DASAR - Anak Agung Istri Mas Wiryani; Ida Bagus Yoga Swadnyana; I Wayan Sujana; Dharia Rizkyla Ramadhani; Ni Putu Oktavia Kusuma Sari (STKIP Subang, 2026)
This study is motivated by the limited use of local wisdom-based learning media in elementary schools, resulting in less engaging learning and suboptimal character development among students. This study aims to develop a digital flipbook based on local wisdom through the Balinese folktale I Cupak and Gerantang, presented in the form of text and images, and to ensure that it meets valid and practical criteria. The method used is research and development based on the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study include material experts, instructional design experts, media experts, and fourth-grade students at SD Negeri 11 Pedungan. Data were collected through interviews, documentation, and questionnaires, and then analyzed using percentage techniques. The results indicate that the developed digital flipbook is categorized as highly valid and highly practical. This media is able to enhance student engagement, facilitate understanding of the story content, and support more interesting and meaningful learning. Therefore, the developed media can be used as an alternative local wisdom-based learning medium in elementary schools.